2014
DOI: 10.1155/2014/860180
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Loranthus parasiticus on Scopolamine‐Induced Memory Impairment in Mice

Abstract: This study is undertaken to evaluate cognitive enhancing effect and neuroprotective effect of Loranthus parasiticus. Cognitive enhancing effect of Loranthus parasiticus was investigated on scopolamine-induced amnesia model in Morris water maze test and passive avoidance test. We also examined the neuroprotective effect on glutamate-induced cell death in HT22 cells by MTT assay. These results of Morris water maze test and passive avoidance test indicated that 10 and 50 mg/kg of Loranthus parasiticus reversed sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In this test for acquisition trial a decrease in EL & increase in TSTQ on 7 th and 14 th days and for probe trial an increase in TSTQ & TSA on 14 th day indicated improvement of spatial learning and memory of rats as compared to disease control and control group. In the study on the effects of Loranthus parasiticus on scopolamine-induced memory impairment in mice almost same outcomes were reported by Weon et al, [39].…”
Section: Discussionsupporting
confidence: 74%
“…In this test for acquisition trial a decrease in EL & increase in TSTQ on 7 th and 14 th days and for probe trial an increase in TSTQ & TSA on 14 th day indicated improvement of spatial learning and memory of rats as compared to disease control and control group. In the study on the effects of Loranthus parasiticus on scopolamine-induced memory impairment in mice almost same outcomes were reported by Weon et al, [39].…”
Section: Discussionsupporting
confidence: 74%
“…In PA test an increase in STL on 7 th (after 24 hrs of EL) and 12 th , 13 th , 14 th day (after 24, 48 and 72 hrs of EL) after the acquisition trial indicated improvement of learning and memory of rats as compared to control rats. In the study on Loranthus parasiticus on scopolamine-induced memory impairment in mice by Weon et al, stated increased latency time in this test [54]. MWM test is widely used behavioral tests for studying hippocampus-dependent spatial memory and leaning.…”
Section: Discussionmentioning
confidence: 98%
“…This generated H 2 O 2 is less damaging, although the catalase and gluthatione peroxidase systems can neutralize the H 2 O 2 by converting it to H 2 O and O 2 [57]. CAT is a glycoprotein present in the antioxidant defense system of all cells that protects the cell from oxidative damage done by ROS [54]. It catalyzes the breakdown of H 2 O 2 to H 2 O and O 2 and protects the cell from highly reactive hydroxyl radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weighed quantity of EEPE was suspended in normal saline (pH 7.4) and administered orally to rats at 100 and 200 mg/kg b.w. The duration of the study and doses of donepezil hydrochloride and EEPE were adjusted based on literature searches [39,40] . Every day, standard drug and the suspension of extract were prepared freshly and administered before 30 min of the experiment.…”
Section: Administration Of Drugs and Test Compoundsmentioning
confidence: 99%